The Community Adaptation Strategies to Tidal Floods (Case Study: Karangjompo Community, Tirto Sub-District, Pekalongan Regency) - Hijriyanti, Fatlina; Nurhadi; Siregar, Riadi Syafutra (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The occurence of tidal floods, which are a result of rising sea levels, affects the lives of the surrounding community. One of the areas frequently affected by tidal floods is Karangjompo Village, located in the northern part of Pekalongan Regency. Due to the impacts of tidal floods on residential areas, the village community needs to strategize to adapt and ensure their survival. Failure to address the challenges and issues caused by tidal floods may lead to new social problems. Therefore, the formulation of this research is to explore the adaptation strategies implemented by the community in Karangjompo Village towards tidal floods. The method used in this research is qualitative, aiming to provide a clear overview of the adaptation strategies employed by the Karangjompo community. The findings indicate that the community adopts various strategies such as periodically raising house floors, preparing door barriers during flood-prone months, purchasing or making their own boats for transportation during floods, evacuating, collaborating with various parties, and maintaining solidarity and mutual assistance among community members.